Two sympatric new species of Phrynopus (Anura: Strabomantidae) from Yanachaga Chemillen National Park (central Peruvian Andes) - Chaparro, Juan C.; Padial, Jose M.; de La Riva, Ignacio (Zootaxa, 2008)
Two sympatric new species of Phrynopus (Anura: Strabomantidae) are described from elfin forests and puna grasslands (3363–3589 m) of the eastern slopes of the Andes of Departamento Pasco in central Peru. Phrynopus miroslawae sp. nov. is a medium-sized species characterized by lacking vomerine teeth and tympanic membrane, and by having dorsolateral folds, areolate ventral skin, dorsum gray with black spots, venter cream with small scattered black blotches, and iris bronze. Phrynopus nicoleae sp. nov. is a small species characterized by lacking tympanic membrane and by having vomerine teeth, an X-shaped middorsal fold, ventral skin areolate, dorsum tan with black stripes and bluish tubercles, and iris bronze with black reticulations.